Overcoming fear of movement resulting from knee replacement; strategies used by patients: An interview study. (May 2022) - Najafi, Fatemeh; Zare, Zahra; Javad Mortazavi, Seyed Mohammad; Lundberg, Mari; Shahsavari, Hooman
Abstract: Background and aims: Fear of movement is among the main concerns of patients following knee replacement surgery and a determining factor in the success of surgery. The strategies adopted by patients to overcome this fear have not yet been identified, but once pin pointed, these strategies can be strengthened and modified through intervention. The aim of the present study was to explore the personal strategies adopted by patients following knee replacement to overcome fear of movement. Materials and methods: Interviews were conducted with 15 patients who had undergone knee replacement, selected by purposive sampling. Data were collected through in-depth semi-structured interviews and analyzed using inductive content analysis. Results: The patients' strategies as depicted in their narratives were classified into three categories: 1) Movement based on awareness; 2) Movement based on support; and 3) Movement based on hope. These three categories are described in eight subcategories and show what strategies the patients used to overcome their fear of movement. Conclusion: These findings can help to increase awareness about strategies to overcome fear of movement in patients following knee replacement and to develop and support tailored treatment strategies with the aim of reducing such fear of movement and increasing physical activity among the patients.